Major signaling pathways in migrating neuroblasts - Khodosevich, Konstantin; Seeburg, Peter H.; Monyer, Hannah (Frontiers in Molecular Neuroscience, 2009)
Neuronal migration is a key process in the developing and adult brain. Numerous factors act on intracellular cascades of migrating neurons and regulate the final position of neurons. One robust migration route persists postnatally – the rostral migratory stream (RMS). To identify genes that govern neuronal migration in this unique structure, we isolated RMS neuroblasts by making use of transgenic mice that express EGFP in this cell population and performed microarray analysis on RNA. We compared gene expression patterns of neuroblasts obtained from two sites of the RMS, one closer to the site of origin, the subventricular zone (SVZ), and one closer to the site of the final destination, the olfactory bulb (OB). We identified more than 400 upregulated genes, many of which were not known to be involved in migration. These genes were grouped into functional networks by bioinformatics analysis. Selecting a specific upregulated intracellular network, the cytoskeleton pathway, we confirmed by functional in vitro and in vivo analysis that the identified genes of this network affected RMS neuroblast migration. Based on the validity of this approach, we chose four new networks and tested by functional in vivo analysis their involvement in neuroblast migration. Thus, knockdown of Calm1, Gria1 (GluA1) and Camk4 (calmodulin-signaling network), Hdac2 and Hsbp1 (Akt1-DNA transcription network), Vav3 and Ppm1a (growth factor signaling network) affected neuroblast migration to the OB.